2006
DOI: 10.1007/s10637-006-9004-9
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide in patients with hepatocellular carcinoma: a phase II trial

Abstract: Single-agent arsenic trioxide using this dose schedule is not active against advanced HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 23 publications
1
85
0
1
Order By: Relevance
“…The anticancer activity of arsenic is well known and resulted in the recent approval of ATO against APL (1). However, the activity of ATO against solid cancer types is so far rather limited (8)(9)(10)(11)40). Some recent reports indicate that exposure to inorganic arsenic salts leads to activation of EGFR in nonmalignant as well as in malignant cells, for example, via c-Src kinase-mediated signals (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer activity of arsenic is well known and resulted in the recent approval of ATO against APL (1). However, the activity of ATO against solid cancer types is so far rather limited (8)(9)(10)(11)40). Some recent reports indicate that exposure to inorganic arsenic salts leads to activation of EGFR in nonmalignant as well as in malignant cells, for example, via c-Src kinase-mediated signals (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of its successful clinical application, the anticancer activity of ATO either as monotreatment or in combination with other agents was also intensively studied in various other hematologic malignancies (5,6) and several solid cancer types (7). However, reports from phase II clinical trials on patients with hepatocellular carcinoma (HCC), metastatic renal cell carcinoma, and metastatic melanoma suggested so far that ATO has only limited efficacy against solid tumors (8)(9)(10)(11)(12). Although multiple resistance mechanisms for arsenic have been described on the cellular level (1), the reasons underlying the lack of efficacy of ATO in solid tumor types are still widely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Promising in vitro effects of ATO on gastric cancer (8), HNSCC (9), neuroblastoma (10), esophageal (11), prostate and ovarian carcinomas (12) have been reported. Furthermore, Phase II studies of ATO in patients with relapsed or refractory multiple myeloma (13), metastatic melanoma (14), hepatocellular carcinoma (15) and myelodysplatic syndromes (16) have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has also been used in therapy for solid tumors such as HCC, gastric cancer, colorectal cancer, and renal cancer (18)(19)(20). Although a significant anti-cancer effect had been reported in preclinical and clinical trials, failure of chemotherapy was reported frequently in patients and some cell lines (5). Among the reasons anti-cancer drugs fail, the most common is acquired drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Years before the noticeable anti-cancer activity of arsenic trioxide attracted the attention of oncologists, the effective therapeutic results in vitro and in vivo were surprising. However, recently a phase II trial evaluating the efficacy and toxicity of arsenic trioxide in patients with HCC showed that single-agent arsenic trioxide is pool active against advanced HCC (5). Although several likely factors could explain the inefficacy of arsenic trioxide against advanced HCC, the appearance of drug resistance might be an important possibility.…”
Section: Introductionmentioning
confidence: 99%